2016
DOI: 10.1002/prot.24975
|View full text |Cite
|
Sign up to set email alerts
|

Contact‐assisted protein structure modeling by global optimization in CASP11

Abstract: We have applied the conformational space annealing method to the contact-assisted protein structure modeling in CASP11. For Tp targets, where predicted residue-residue contact information was provided, the contact energy term in the form of the Lorentzian function was implemented together with the physical energy terms used in our template-free modeling of proteins. Although we observed some structural improvement of Tp models over the models predicted without the Tp information, the improvement was not substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Data set N1008 was designed to test the ability to combine backbone‐only assignments with advanced structure prediction methods. Several studies have previously explored the combination of sparse NMR data obtained on perdeuterated protein samples with advanced molecular modeling methods . For such data sets, the NOESY cross peak assignments are not complicated by the presence of unassigned sidechain resonances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data set N1008 was designed to test the ability to combine backbone‐only assignments with advanced structure prediction methods. Several studies have previously explored the combination of sparse NMR data obtained on perdeuterated protein samples with advanced molecular modeling methods . For such data sets, the NOESY cross peak assignments are not complicated by the presence of unassigned sidechain resonances.…”
Section: Resultsmentioning
confidence: 99%
“…During the CASP10 International Meeting, it was suggested that rather than using predicted contacts, which at the time were not very reliable, it might be more productive to explore the impact of a few real experimental contacts, as can be obtained from NMR, cross‐linking, fluorescence energy transfer, or other experimental methods. This concept developed in CASP11 into the first NMR‐assisted contact prediction experiment . In the meantime, the accuracy of contact prediction based on evolutionary sequence covariance analysis and machine learning has increased dramatically, making the original proposal of replacing predicted contacts with real, sparse experimental contacts moot.…”
Section: Introductionmentioning
confidence: 99%
“…For the modeling of Tx targets, we introduced a flat‐bottom Lorentzian‐function‐based contact energy term, ETx as follows: ETx=ijNtrue{leftwij(rijrupper)2(rijrupper)2+normalσ2,rij>rupperleft0,otherwise where the summation is over all N given cross‐linking pairs between residue indices of i and j , r ij is the distance between two Cnormalα atoms of residues i and j . The energy weight parameter w ij is set to 24.0 × confidence score which was given in the cross‐linking data where the 24.0 value was determined by analysis for CASP11 Tx targets.…”
Section: Methodsmentioning
confidence: 95%
“…Since CASP7, we formulated protein 3D modeling in terms of 3 layers of combinatorial optimization problems; multiple sequence alignment, chain building using the alignment containing multiple templates, and side‐chain remodeling . When solving each combinatorial problem, due to the intrinsic nature of solving frustrated systems, obtaining a solution that satisfies all the restraints applied is seemingly impossible.…”
Section: Discussionmentioning
confidence: 99%
“…A flat‐bottom Lorentzian‐function‐based contact energy term was implemented as follows: Econtact=ijNtrue{left(rijrcut)2(rijrcut)2+normalσcontact2ctrue(ptrue),rijrcutleft0,otherwise, ctrue(ptrue)=ap+1, where the summation is over all N MetaPSICOV predictions with p > 0.2, and i and j correspond to the residue indices of the predicted contact. Here, r ij is the distance between 2 C β atoms of residues i and j .…”
Section: Methodsmentioning
confidence: 99%